2003
DOI: 10.1103/physrevd.68.105001
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarization and color superconductivity in quark matter

Abstract: A coexistent phase of spin polarization and color superconductivity in high-density QCD is investigated using a self-consistent mean-field method at zero temperature. The axial-vector self-energy stemming from the Fock exchange term of the one-gluon-exchange interaction has a central role to cause spin polarization. The magnitude of spin polarization is determined by the coupled Schwinger-Dyson equations with a superconducting gap function. As a significant feature, the Fermi surface is deformed by the axial-v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 41 publications
1
100
0
Order By: Relevance
“…Note also that one should distinguish between the spontaneous deformation of Fermi-surfaces and explicit breaking of rotational symmetry by external fields. In the latter case the initial Lagrangian contains term(s) that explicitely break the symmetry and the resulting anisotropy of the self-energies can be interpreted as a deformation of the Fermi surfaces [19]. These type of deformations are interaction induced and are unrelated to the spontaneous deformations that appear even if the interaction is O(3) symmetric.…”
Section: Dfs Phasementioning
confidence: 99%
“…Note also that one should distinguish between the spontaneous deformation of Fermi-surfaces and explicit breaking of rotational symmetry by external fields. In the latter case the initial Lagrangian contains term(s) that explicitely break the symmetry and the resulting anisotropy of the self-energies can be interpreted as a deformation of the Fermi surfaces [19]. These type of deformations are interaction induced and are unrelated to the spontaneous deformations that appear even if the interaction is O(3) symmetric.…”
Section: Dfs Phasementioning
confidence: 99%
“…We have considered the possibility of ferromagnetism in quark matter interacting with the one-gluon-exchange (OGE) interaction [5] or with an effective interaction [6], and suggested that quark matter has a potentiality to be spontaneously polarized. To understand the magnetic properties of quark matter more realistically , especially near the critical point, some non-perturbative consideration about the instability of the Fermi surface is indispensable.…”
Section: Relativistic Ferromagnetismmentioning
confidence: 99%
“…The choice of M M determines detection efficiencies and waveform parameter resolutions. Some template construction methods for a given M M have already been proposed as [19], [20,21]. In a realistic search, however, non-stationary noises in detector outputs would reduce SNRs, so it is not clear whether the criterion ≥ M M is still fulfilled.…”
Section: Introductionmentioning
confidence: 99%
“…Arnaud et al discussed a general template construction method for matched filtering searches and its application to the ringdown case [19]. Recently Nakano et al proposed an efficient tiling method for ringdown filters [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation